PjBL Learning Training Based on Science Practicum Tools for Vernier Calipers and Screw Micrometers at Pondok Pesantren Attohiriyah Alfadiliyah Bodak - Aris Doyan; Susilawati Susilawati; Yayuk Andayani; Muntari Muntari; Mahrus Mahrus; Fitriana Lugi (Pascasarjana Universitas Mataram, 2023)
PjBL learning training based on practicum tools and learning videos on caliper material and screw micrometers at the Attohiriyah Alfadiliyah Islamic Boarding School, Bodak, Central Lombok. Measurement using a screw micrometer and caliper is one of the materials taught in high school physics subjects. The problem faced is the tool's small size, making it difficult for students when the teacher demonstrates the tool. The solution that can be offered is to watch the learning videos on how to read caliper calipers and screw micrometers on a computer or mobile phone and can be demonstrated directly with measuring instruments. The use of visual aids and videos in learning really helps the effectiveness and efficiency of delivering messages and lesson content. The use of tools and videos of caliper and screw micrometer visual aids in learning effectively increases the average student understanding of the concept of measurement